Bacterial communities in trace metal contaminated lake sediments are dominated by endospore-forming bacteria - Sauvain, Loïc; Bueche, Matthieu; Junier, Thomas; Masson, Matthieu; Wunderlin, Tina; Kohler-Milleret, Roxane; Gascon Diez, Elena; Loizeau, Jean-Luc; Tercier-Waeber, Mary-Lou; Junier, Pilar (My University, 2014)
Lake sediments in areas close to the outlet of wastewater treatment plants are sinks for pollutants. Bacterial communities in sediments are likely affected by the released effluents, but in turn they might modify the distribution and bioavailability of pollutants. On the shore of Lake Geneva, Switzerland, wastewater from the City of Lausanne is treated and discharged into the lake via an outlet pipe in the Vidy Bay. The objectives of this study were to assess (1) the impact of the treated wastewater release on the bacterial communities in the Vidy Bay sediments and (2) the potential link between bacterial communities and trace metal sediment content. Bacterial community composition and abundance were assessed in sediments collected in three areas with different levels of contamination. The main factors affecting bacterial communities were inferred by linking biological data with chemical analyses on these sediments. Near to the outlet pipe, large quantities of bacterial cells were detected in the three upper most cm (3.2 × 109 cells assessed by microscopy and 1.7 × 1010 copies of the 16S rRNA gene assessed by quantitative PCR, per gram of wet sediment), and the dominant bacterial groups were those typically found in activated sludge (e.g. Acidovorax defluivii and Hydrogenophaga caeni). Three samples in an area further away from the outlet and one sample close to it were characterized by 50 % of endospore-forming Firmicutes (Clostridium spp.) and a clear enrichment in trace metal content. These results highlight the potential role of endospore-forming Firmicutes on transport and deposition of trace metals in sediments.
Keywords: Sediments; Bacterial communities; Firmicutes; Trace metals; High-throughput DNA sequencing; Lake Geneva